Evaluation of stroke risk factors and characteristics in the comorbidity of cancer (Annals of Medical Research, 2021)
Aim: Stroke and cancer can be followed together and in the presence of cancer, there may be changes in classical stroke characteristics. The aim of this study was to determine the effect of cancer on stroke risk factors, radiological and clinical features.Materials and Methods: Patients who were hospitalized with the diagnosis of stroke between 2014-2020 were included in the studyretrospectively. By examining the stroke and cancer characteristics of the patients; The differences in demographic findings, stroke risk factors, and radiological features of stroke between patients with and without cancer were examined. The anti-cancer treatments used and the characteristics of cancer were evaluated in stroke patients.Results: 281 stroke patients were evaluated and cancer was detected in 52 patients. There was no significant difference in terms of demographic characteristics of the patients. No significant difference was observed in stroke patients with cancer in terms of risk  factors except smoking and alcohol use. Multiple ischemic lesions were more evident on magnetic resonance imaging (MRI) in stroke patients with cancer. The most common cancer was lung cancer.Conclusion: Stroke and cancer are increasingly common comorbidities. As the time between stroke and cancer development decreases, while the risk factors for cancer are more prominent, classical risk factors for stroke are observed less frequently.